Numbering singing approach used in backup singing / Iffah Izzati Baharudin - Baharudin, Iffah Izzati (2018)
Back up singing is often a career where singers often indulge in as part of their exposure to the music industry. University students who major in voice sometimes do back up singing for live performances or for recording in the studios. Performing as backup singers require some knowledge in supporting the main vocal line. Planning how the vocal support will be for the different songs to be performed needs to be discussed and practiced. Usually backup singers will need to notate what they are supposed to sing on the lyric sheet. The purpose of this study was therefore to explore the numbering singing approach used in backup singing. On the other hand, this study also investigates all the approaches on notating voicings that have been used in backup singing. Sample consisted of four professional backup vocalists who are active in the Malaysian music industry. How the numbering singing approach can be taught to novice backup singers is also looked at.